The Large Hadron Collider Unraveling the Mysteries of the Universe - Beech, Martin; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2010)
The Large Hadron Collider (LHC) is the largest engineering project ever undertaken, and one of the most expensive. Why are physicists around the world so excited about it? What secrets of the universe does this gargantuan piece of machinery hope to reveal? What risks are there in operating it? Could the exotic particles that are produced in the collisions$1 (Bincluding tiny black holes that should wink into and out of existence$1 (Bbetween subatomic particles be a threat not only to humankind but to the planet itself? In this thorough and engaging review of cutting-edge physics and cosmology, you will learn why the collider was built and how it works. You will find out what scientists are hoping to find out and what current aspects of the Standard Model might need to be revised. You will even learn about the quest to identify so-called dark matter and dark energy, which many now feel make up most of what's out there. This is a wild ride into some very unfamiliar and strange territory, but it is well worth your time to explore, as the Large Hadron Collider is set to change some very fundamental ideas of our universe, from the smallest pieces that make it up to the grandest.s
The Story of Matter -- The World$1 (Bs Most Complicated Machine -- The Standard Model, the Higgs, and Beyond -- The Big Bang and the First 380,000 Years -- Dark Matters -- Dark Energy and an Accelerating Universe -- The Waiting Game.s
Keywords: Physics; Astronomy; Particle acceleration; Mathematics; Physics; Particle Acceleration and Detection, Beam Physics; Popular Science in Mathematics/Computer Science/Natural Science/Technology.; Astronomy, Astrophysics and Cosmology